The Relationship Between Sodium, Potassium Intake and Nutritional Status with Blood Pressure in Hypertension Sufferers in the Loa Janan Community Health Center Working Area - Aulia, Desy; Saraheni; Wahyuningrum, Diah Retno (Indonesian Journal of Advanced Research, 2023)
Riskesdas data 2018 shows that the prevalence of hypertension in the elderly population >18 years in Indonesia based on national measurements is 34.11%. The aim of the research was to determine the relationship between sodium, potassium intake and nutritional status with blood pressure in hypertension sufferers in the Loa Janan Community Health Center working area. The research method was cross sectional with accidental sampling technique consisting of 45 respondents. Data collection technique using 24 hour food recall interviews for 2 days. Chi square test data analysis technique. The results of the chi square test showed that there was a significant relationship between sodium intake and blood pressure (p=0.000), there was no significant relationship between potassium intake and blood pressure (p=0.509) and there was a significant relationship between nutritional status and blood pressure (p =0.007). Conclusion: There is a significant relationship between sodium intake and blood pressure, and there is no significant relationship between potassium intake and blood pressure and there is a significant relationship between nutritional status and blood pressure in the Loa Janan Community Health Center working area.